EXPLORATION OF LINGUISTIC ASPECTS OF IDIOMS AND TEACHING PROBLEMS WITH THEM (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Idiomatic expressions are the key point of effective communication in any language, especially in English. However, using them can be a bit challenging for learners as these expressions often cannot be translated with their literal meaning. This article aims to explore the importance of idioms in everyday language, their role in enhancing communication and strategies for mastering them with interactive methods. Using and understanding is not only significant for fluency but also for cultural bridge and social interaction.